2018
DOI: 10.1371/journal.pone.0196070
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of exposure of endangered Caspian seals to Canine distemper virus, Leptospira interrogans, and Toxoplasma gondii

Abstract: Canine distemper virus (CDV), Leptospira interrogans, and Toxoplasma gondii are potentially lethal pathogens associated with decline in marine mammal populations. The Caspian Sea is home for the endangered Caspian seal (Pusa caspica). In the late 1990s and early 2000s, CDV caused a series of mortality events involving at least several thousand Caspian seals. To assess current infection status in Caspian seals, we surveyed for antibodies to three pathogens with potential to cause mortality in marine mammals. Du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 30 publications
0
3
0
1
Order By: Relevance
“…In the current work, no morbillivirus contigs were recovered from metagenomic sequencing of samples 2009-2020, and the were no positive detections by RT-PCR for 2019-2020 samples. Together, our two studies and others[90], suggest that CDV has circulated episodically in Caspian seals since 2001, but the trigger mechanisms for mass mortalities are still unknown.…”
supporting
confidence: 66%
“…In the current work, no morbillivirus contigs were recovered from metagenomic sequencing of samples 2009-2020, and the were no positive detections by RT-PCR for 2019-2020 samples. Together, our two studies and others[90], suggest that CDV has circulated episodically in Caspian seals since 2001, but the trigger mechanisms for mass mortalities are still unknown.…”
supporting
confidence: 66%
“…in the sirenian Peruvian Amazon manatees ( Trichechus inunguis ) [18] as well as in pinnipeds including harbor seals ( Phoca vitulina ) [19, 20], Northern elephant seals ( Mirounga angustirostris ) [21], California sea lions ( Zalophus californianus ) [2226, 17], and Chilean South American sea lions ( Otaria byronia ) [27]. Most recently, two serovars – Pomona and Calicola – of Leptospira interrogans were detected in serum samples of endangered Caspian seals ( Pusa caspica ) in the Caspian Sea off Northern Iran [28]. Information on the prevalence of Leptospira in cetaceans is scarce, with the first isolation of the proposed L. brihuegai sp.…”
Section: Introductionmentioning
confidence: 99%
“…10 The occurrence of canine distemper is common in different parts of Iran [11][12][13][14] and there is a report of contamination of Caspian seals with CDV. 15 Recently, the prevalence of distemper disease in dogs in Mashhad (the location of this report) has been determined to be 4% (unpublished data). However, the prevalence of it in Iranian wildlife is unknown.…”
Section: Introductionmentioning
confidence: 90%
“…reported that other wildlife in each area may be the reservoir of CDV other than dogs, and that hyenas may get the virus from other wild animals or transmit it to other wild animals and domestic dogs 10 . The occurrence of canine distemper is common in different parts of Iran 11–14 and there is a report of contamination of Caspian seals with CDV 15 . Recently, the prevalence of distemper disease in dogs in Mashhad (the location of this report) has been determined to be 4% (unpublished data).…”
Section: Introductionmentioning
confidence: 99%